Peritonectomy and hyperthermic intraperitoneal chemotherapy: Cost analysis and sustainability. Issue 3 (March 2015) - Bagnoli, Pietro F.; Cananzi, F.C.M.; Brocchi, A.; Ardito, A.; Strada, D.; Cozzaglio, L.; Mussi, C.; Brusa, S.; Carlino, C.; Borrelli, B.; Alemanno, F.; Quagliuolo, V.
Abstract Background Malignancies of the peritoneum remain a challenge in any hospital that accepts to manage them, due not only to difficulties associated with the complexity of the procedures involved but also the costs, which – in Italy and other countries that use a diagnosis-related group (DRG) system – are not adequately reimbursed. Material and methods We analyzed data relative to 24 patients operated on between September 2010 and May 2013 with special regard to operating room expenditure, ICU stay, duration of hospitalization, and DRG reimbursement. The total costs per patient included clinical, operating room, procedure, pathology, imaging, ward care, allied healthcare, pharmaceutical, and ICU costs. Results Postoperative hospital stay, drugs and materials, and operating room occupancy were the main factors affecting the expenditure for cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. We had a median hospitalization of 14 days, median ICU stay of 2.4 days, and median operating room occupancy of 585 min. The median expenditure for each case was € 21, 744; the median reimbursement by the national health system € 8, 375. Conclusions In a DRG reimbursement system, the economic effort in the management of patients undergoing peritonectomy procedures may not be counterbalanced by adequate reimbursement. Joint efforts between medical and administration parties are mandatory to develop appropriate treatment protocols and keep down the costs.